Ecological Study of the Moss Community and Microorganisms in the Vicinity of Syowa Station, Antarctica - マツダ, タツロウ; MATSUDA, Tatsuro (1968)
P(論文) This paper discusses the environment and ecology of moss community and microoganisms of East Ongul Island, West Ongul Island, Ongul Kalven Island and Soya Coast, in the Antarctic. Moss community was distributed mainly on the west side of the islands and developed on the southwest slope. Growth form of cushion of moss community is discussed. Blue green algae coexisted with these mosses and restrained the growth of each individual. Microclimate of moss cushion was measured with a self-recording thermistor throughout the year. Various microorganisms were found in the water contained in the moss community and ecological observations were conducted. Discussions were given to ecosystem existing among the terrestrial vegetations, sea birds and sea creatures. departmental bulletin paper